Exploring Challenges in Implementing Differentiated Instruction for Vulnerable Students - Baraily, Khagendra; Sherpa, Dawa (Perspectives on Higher Education, 2024)
The regular class comprises students with various needs, interests and learning capacities. The learning achievement seems to be at different levels due to diverse needs. The lecture method is the choice of almost every teacher due to their unchanged thought in teaching. This study explores the lived experience of a teacher using differentiated instruction in class and the challenges faced in adopting differentiated instruction. The research design employed for this study is qualitative with hermeneutics phenomenology, which depicts the challenges experienced by teachers while teaching in the regular classroom. Four teachers from the community school in Morang district, one of the eastern districts of Koshi province, were purposively selected for the interview with written consent. The interview was transcribed and coded for the thematic process. The transcription was read and reread more times and categorized to generate a basic theme. The themes are further reorganized by searching for commonalities to extract a global theme that was described as the intersection of a theoretical construct. The challenges explored from the perception are inadequacy of training, content modification, excessive workload, resiliency in inner management, lack of time management, the effect of large class size, and inflexibility in time and resource lack of knowledge for instructional planning. The finding contributes to adopting instructional strategies and creating an inclusive environment in the school. This also becomes a milestone for implementing diversity management strategies to address the diverse needs of learners.